Smoking ; Blanco x 7 [videorecording] - Lazaro, Cheche (Quezon City Probe Production, 1988)
Looks into the effects of smoking ban in Quezon City and the extremely talented family of seven who paint for a living.
Smoking (18 min.) -- Blanco x 7 (15 min.)
VHS.
Keywords: Blanco, Jose -- Interviews; Smoking -- Law and legislation -- Philippines; Artists, Filipino